2018
DOI: 10.1523/eneuro.0315-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-Weighted Integration of Audiovisual Signals Can Be Modulated by Top-down Attention

Abstract: Behaviorally, it is well established that human observers integrate signals near-optimally weighted in proportion to their reliabilities as predicted by maximum likelihood estimation. Yet, despite abundant behavioral evidence, it is unclear how the human brain accomplishes this feat. In a spatial ventriloquist paradigm, participants were presented with auditory, visual, and audiovisual signals and reported the location of the auditory or the visual signal. Combining psychophysics, multivariate functional MRI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 93 publications
(137 reference statements)
3
64
0
1
Order By: Relevance
“…Our data indeed support this conclusion, as parietal activity within the audio-visual trial was encoding the behaviorally combined information more than the acoustic information. Previous work has shown that parietal activity combines multisensory information flexibly depending on task-relevance and crossmodal disparity (30,34) and the focus on reporting the sound location in our task may have led to the attenuation of the combined visual information in the subsequent trial. Future work is required to better understand the influence of task-relevance on uni- and multisensory representations and how these are maintained over time.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our data indeed support this conclusion, as parietal activity within the audio-visual trial was encoding the behaviorally combined information more than the acoustic information. Previous work has shown that parietal activity combines multisensory information flexibly depending on task-relevance and crossmodal disparity (30,34) and the focus on reporting the sound location in our task may have led to the attenuation of the combined visual information in the subsequent trial. Future work is required to better understand the influence of task-relevance on uni- and multisensory representations and how these are maintained over time.…”
Section: Discussionmentioning
confidence: 94%
“…These regions are in line with previous studies, which have pinpointed superior temporal regions, the insula and parietal-occipital areas as hubs for multisensory integration (11,26,27,47). In particular, a series of studies revealed that both temporal and parietal regions combine audio-visual information in a reliability- and task- dependent manner (30,31,34,48). However, while posterior parietal regions reflect the automatic fusion of multisensory information, more anterior parietal regions reflected an adaptive multisensory representation that follows predictions of Bayesian inference models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, fMRI and EEG research jointly suggest that computations involving unisensory estimates rely on lower-level regions at earlier latencies, while Bayesian Causal Inference estimates that take into account the world's causal structure arise later in higher-level cortical regions. Previous fMRI research implicated prefrontal cortices in the computations of the causal structure 28,39 , which may in turn inform the integration processes in parietal and temporal cortices 40 .…”
Section: Discussionmentioning
confidence: 99%
“…the "weighted connections" model of multisensory integration. In this model, the relative reliability of the AMUSIA AND LANGUAGE PROCESSING modalities involved with perception of a stimulus is related to differential connectivity strength (Beauchamp et al, 2010;Rohe and Noppeney, 2018). For example, when participants simultaneously view and feel touches to the hand and reliability of visual and tactile perception is manipulated experimentally via introduction of noise, connection strength (effective connectivity measured with functional MRI and structural equation modeling) between unimodal and multimodal sensory areas adjusts accordingly.…”
Section: [H1] Introductionmentioning
confidence: 99%